Constraints on Higgs boson properties using WW∗(→eνμν)jj production in 36.1fb−1 of √s=13 TeV pp collisions with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bartels, Falk; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Napolitano, Fabrizio; Ott, Philipp; Rassloff, Damir Fabrice; Schultz-Coulon, Hans-Christian; Spieker, Thomas; et al. (The European physical journal. C, Particles and fields, 2022)
This article presents the results of two studies of Higgs boson properties using the $$WW^*(→ eν μ ν )jj$$final state, based on a dataset corresponding to $${36.1}{{fb}^{-1}}$$of $$\sqrt{s}=13$$ TeV proton-proton collisions recorded by the ATLAS experiment at the Large Hadron Collider. The first study targets Higgs boson production via gluon-gluon fusion and constrains the CP properties of the effective Higgs-gluon interaction. Using angular distributions and the overall rate, a value of $$\tan (α ) = 0.0 ± 0.4 (stat.) ± 0.3 (syst.)$$is obtained for the tangent of the mixing angle for CP-even and CP-odd contributions. The second study exploits the vector-boson fusion production mechanism to probe the Higgs boson couplings to longitudinally and transversely polarised W and Z bosons in both the production and the decay of the Higgs boson; these couplings have not been directly constrained previously. The polarisation-dependent coupling-strength scale factors are defined as the ratios of the measured polarisation-dependent coupling strengths to those predicted by the Standard Model, and are determined using rate and kinematic information to be $$a_L=0.91^{+0.10}_{-0.18}$$(stat.)$$^{+0.09}_{-0.17}$$(syst.) and $$a_{T}=1.2 ± 0.4 $$(stat.)$$ ^{+0.2}_{-0.3} $$(syst.). These coupling strengths are translated into pseudo-observables, resulting in $$κ _{VV}= 0.91^{+0.10}_{-0.18}$$(stat.)$$^{+0.09}_{-0.17}$$(syst.) and $$ε _{VV} =0.13^{+0.28}_{-0.20}$$(stat.)$$^{+0.08}_{-0.10}$$(syst.). All results are consistent with the Standard Model predictions.
Im Titel seht der Buchstabe s unter dem Wurzelsymbol
Im Titel ist das Zeichen * und die Zahl "-1" hochgestellt
*ATLAS Collaboration: G. Aad, V. Andrei, F. Bartels, M. Dunford, S. Franchino, M. Klassen, T. Mkrytchyan, F. Napolitano, P. Ott, D.F. Rassloff, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S.M. Weber, M. Wessels, X. Yue [und sehr viele weitere Personen]
Gesehen am 02.02.2023